A versatile isothermal amplification assay for the detection of leptospires from various sample types - Othman, Shuhaidah; Lee, Pui-Yuei; Lam, Jia-Yong; Philip, Noraini; Azhari, Nurul Natasya; Affendy, Norliza Bahtiar; Masri, Siti Norbaya; Neela, Vasantha Kumari; Mohd-Taib, Farah Shafawati; Chee, Hui-Yee (PeerJ, 2022)
Background: Leptospirosis is a zoonotic disease caused by bacteria of the genus Leptospira that affects both humans and animals worldwide. Early detection of the pathogen in humans is crucial for early intervention and control of the progression of the disease to a severe state. It is also vitally important to be able to detect the presence of the pathogen in carrier animals to control the spread of the disease from the environment. Here we developed a simple and rapid loop-mediated isothermal amplification (LAMP) assay targeting the leptospiral secY gene. Results: Several reaction conditions of the LAMP reaction were optimized to ensure efficient amplification of the target DNA. The sensitivity of the developed LAMP assay obtained using a pure Leptospira culture was 2 × 104 copies of genomic DNA per reaction (equivalent to 0.1 ng) for a 40-minute reaction time. No cross-reactions were observed in the LAMP reaction against a series of non-leptospiral bacteria, indicating a specific reaction. The applicability of the LAMP assay was demonstrated on human blood and urine specimens collected from suspected leptospirosis patients and rat kidney specimens collected from suspected leptospirosis outbreak areas and high-risk areas. The developed LAMP assay demonstrated a higher detection rate for leptospiral DNA compared with the polymerase chain reaction (PCR) assay, possibly due to the presence of inhibitory substances, especially in rat kidney specimens, to which the PCR method is more susceptible. The present findings also highlight the importance of urine sample collection from patients for routine monitoring of the disease. Conclusions: In short, the developed LAMP assay can serve as a feasible alternative tool for the diagnosis of leptospirosis and be used for epidemiological and environmental surveillance of the disease, considering its robustness, rapidity, sensitivity, and specificity, as demonstrated in this study.